Coverage enhancement methods for LMDS. - Falconer, D.D (IEEE Communications magazine)
The upper SHF and EHF radio bands (above about 20 GHz) offer abundant available bandwidth for access to metropolitan area networks by fixed broadband wireless access (FBWA) systems. However, these systems must withstand significant propagation impairments, especially shadowing by obstacles and rainfall attenuation. We describe the results of propagation measurements and modeling of coverage, and consequences for FBWA system design, notably antenna placement, use of repeaters, and diversity. High (> 90 percent) coverage generally requires line-of-sight placement, although some non-line-of-sight coverage is possible for short distance and with judicious use of repeaters and macrodiversity.